Development of chemic media (chemistry comic) based on problem based learning on chemical bond materials for class x students - Selly Aprilia Nisa; Meli Sartika Silaban; Saronom Silaban (Jurnal Pendidikan Kimia (JPKim), 2022)
This research is a development research that aims to determine the feasibility of chemic media based on problem based learning on chemical bonding material for class X students based on BSNP standards. In this research, a modified ADDIE development model was used where only the analysis, design, development and evaluation stages were carried out. This research will be conducted at the Department of Chemistry State University of Medan, SMAN 1 Secanggang and SMAS Bintang Langkat. The feasibility of the media is seen through a feasibility questionnaire based on the BSNP standard with a Likert scale of 1 to 5. The validity of the chemic media is obtained from the results of the validation of lecturers and teachers, while the respondents' assessment of chemic media is obtained from the results of the assessments of teachers, students, and students. The results obtained indicate that the chemical media developed is valid or feasible to use. This can be seen from the validation data in terms of content, presentation feasibility, language feasibility, graphic feasibility and problem based learning assessment, respectively, obtaining a percentage of 80.83%; 82.50%; 94.38%; 82.19% and 82.14% so that an average percentage of 82.00% is obtained which is included in the very high category. The results of respondents' assessments of chemic media were reviewed based on aspects of appearance, material and benefits which respectively obtained a percentage of 88.96%; 86.73%; and 86.67% with an average percentage of 87.6% which is included in the very high category.Keywords:ADDIE model, Chemic media, Chemical bonding, Problem based learning